2022
DOI: 10.2106/jbjs.21.01053
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Biological Aging and Frailty in Orthopaedics

Abstract: Biological aging can best be conceptualized clinically as a combination of 3 components: frailty, comorbidity, and disability.Despite advancements in the understanding of senescence, chronological age remains the best estimate of biological age. However, a useful exercise for practitioners is to look beyond chronological age in clinical and surgical decision-making.A chronologically aging person does not age biologically at the same rate.The best way to understand frailty is to consider it as a physical phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“… 20 With more elderly patients undergoing orthopedic surgery, there has been increasing evidence that frailty is associated with adverse outcomes. 2 , 7 Due to this association, various instruments have been implemented in attempts to measure and quantify frailty. A recent systematic review by Lemos et al found the Modified Frailty Index to be the most common instrument used among 24 different instruments.…”
Section: Discussionmentioning
confidence: 99%
“… 20 With more elderly patients undergoing orthopedic surgery, there has been increasing evidence that frailty is associated with adverse outcomes. 2 , 7 Due to this association, various instruments have been implemented in attempts to measure and quantify frailty. A recent systematic review by Lemos et al found the Modified Frailty Index to be the most common instrument used among 24 different instruments.…”
Section: Discussionmentioning
confidence: 99%